2019
DOI: 10.1186/s12871-019-0739-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous infusion of lidocaine and dexmedetomidine on inhibiting cough during the tracheal extubation period after thyroid surgery

Abstract: Background Intravenous lidocaine and dexmedetomidine treatments have been proposed as methods for inhibiting cough. We compared the efficacy of intravenous lidocaine and dexmedetomidine treatments on inhibiting cough during the tracheal extubation period after thyroid surgery. Methods One hundred eighty patients undergoing thyroid surgeries were randomly allocated to the LIDO group (received lidocaine 1.5 mg/kg loading, 1.5 mg/kg/h infusion), the DEX group (received dex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
4
27
2
Order By: Relevance
“…This study showed that the spontaneous respiratory recovery time and extubation time increased more significantly in the experimental groups compared with NS group. The dexmedetomidine 0.8μg/kg group had the greatest effect on the spontaneous breathing time and extubation time, which was similar to previous studies [ 4 , 6 8 , 10 , 11 , 14 , 15 , 17 ]. The higher the dose of dexmedetomidine, the greater the effect on the spontaneous breathing time and extubation time of patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study showed that the spontaneous respiratory recovery time and extubation time increased more significantly in the experimental groups compared with NS group. The dexmedetomidine 0.8μg/kg group had the greatest effect on the spontaneous breathing time and extubation time, which was similar to previous studies [ 4 , 6 8 , 10 , 11 , 14 , 15 , 17 ]. The higher the dose of dexmedetomidine, the greater the effect on the spontaneous breathing time and extubation time of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Cough during the recovery period of general anesthesia is a more concerned problem, mainly caused by the stimulation of endotracheal tube, secretions and volatile anesthetics, which not only brings unpleasant feelings to patients, but also accompanies with complications such as laryngospasm, circulation fluctuation, arrhythmia, wound dehiscence and bleeding. Many drugs such as propofol, ketamine, remifentanil and lidocaine have been used to reduce the cough reflex during extubation [ 1 4 ]. Dexmedetomidine is a α 2 adrenergic receptor agonist that can produce sedative and anti-anxiety effects through receptors in the locus coeruleus without respiratory depression [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IV lidocaine has long been studied as an agent to suppress laryngospasm and the cardiovascular response to extubation [ 13 , 34 , 35 ]. However, it should be noted that evidence from other studies has not always supported the efficacy of lidocaine to attenuate or prevent these changes [ 2 ].…”
Section: Pharmacologic Aids Of Tracheal Extubationmentioning
confidence: 99%